2015
DOI: 10.1002/ece3.1438
|View full text |Cite
|
Sign up to set email alerts
|

The stress hormone corticosterone in a marine top predator reflects short‐term changes in food availability

Abstract: In many seabird studies, single annual proxies of prey abundance have been used to explain variability in breeding performance, but much more important is probably the timing of prey availability relative to the breeding season when energy demand is at a maximum. Until now, intraseasonal variation in prey availability has been difficult to quantify in seabirds. Using a state-of-the-art ocean drift model of larval cod Gadus morhua, an important constituent of the diet of common guillemots Uria aalge in the sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
1
17
1
Order By: Relevance
“…, Barrett et al. ), which in turn mediates the changes in foraging behavior (Angelier et al. , , Barger and Kitaysky ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Barrett et al. ), which in turn mediates the changes in foraging behavior (Angelier et al. , , Barger and Kitaysky ).…”
Section: Introductionmentioning
confidence: 99%
“…, Barrett et al. ). A previous study demonstrated that stressful food shortages (years when baseline CORT was elevated) resulted in increased interspecific trophic niche partitioning between murre species during incubation; that is, stable isotopic signatures diverged between species during food‐limited periods (Barger and Kitaysky ).…”
Section: Introductionmentioning
confidence: 99%
“…; Barrett et al. ), negatively impact reproductive performance and adult nutritional status (Dorresteijn et al. ; Barrett et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies find no evidence that changes in prey quality affect reproductive output (Jodice et al 2006;Kadin et al 2012;Hjernquist and Hjernquist, 2010). Others clearly demonstrate that low-quality prey, such as fisheries offal (Gr emillet et al 2008), or changes in the energy content, availability, or abundance of a preferred energy-rich prey species (Wanless et al 2007;Dorresteijn et al 2012;Barrett et al 2015), negatively impact reproductive performance and adult nutritional status (Dorresteijn et al 2012;Barrett et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Food availability has a pronounced effect on stress levels within individuals (Maxwell et al 1992;Clinchy et al 2004;Hinam & St. Clair 2008;Barrett et al 2015). Variation in food abundance was the best predictor of GCs in the common murre (Uria aalge; Kitaysky et al 2007).…”
Section: Using Physiological Measures To Understand Mechanisms Causinmentioning
confidence: 99%